2013
DOI: 10.2147/ijn.s47174
|View full text |Cite
|
Sign up to set email alerts
|

Histologic and apoptotic changes induced by titanium dioxide nanoparticles in the livers of rats

Abstract: Titanium dioxide (TiO 2 ) nanoparticles are among the top five nanoparticles used in consumer products, paints, and pharmaceutical preparations. Given that exposure to such nanoparticles is mainly via the skin and inhalation, the present study was conducted in male Wistar albino rats (Rattus norvegicus). Our aim was to investigate the effect of TiO 2 nanoparticles on hepatic tissue in an attempt to understand their toxicity and the potential effect of their therapeutic and diagnostic use. To investigate the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…NTiO 2 induced apoptosis in mouse epidermal (JB6) and human bronchial epithelial (BEAS-2B) cell lines (27). Alarifi et al have also demonstrated apoptotic effects of NTiO 2 in the liver of rats (28). In the present study, QCT intensively decreased the apoptotic index in the liver of rats exposed to NTiO 2 .…”
Section: Discussionsupporting
confidence: 66%
“…NTiO 2 induced apoptosis in mouse epidermal (JB6) and human bronchial epithelial (BEAS-2B) cell lines (27). Alarifi et al have also demonstrated apoptotic effects of NTiO 2 in the liver of rats (28). In the present study, QCT intensively decreased the apoptotic index in the liver of rats exposed to NTiO 2 .…”
Section: Discussionsupporting
confidence: 66%
“…They are known to enhance superoxide production in osteoblasts [ 16 ]. TiO 2 NPs were shown to interact with proteins and enzymes in hepatic tissues, interfering with antioxidant defense mechanisms and leading to generation of ROS [ 57 ]. Since NADPH oxidase is a major actor of oxidative stress by producing superoxide ions, it was evident that investigating the effect of TiO 2 NPs on this enzyme constitutes a relevant issue.…”
Section: Discussionmentioning
confidence: 99%
“…Paraffin sections (4–5 μm) were stained with hematoxylin and eosin by using the conventional histological and staining method. 15 Stained sections of control and treated mice were observed, and the photos were taken by using the optical microscope to view alterations in the architecture, the hepatocytes, and the sinusoids and to detect the presence of degeneration, necrosis, fatty change, and portal fibrosis.…”
Section: Methodsmentioning
confidence: 99%